A new proposal for laparoscopic left colectomy in a rat model - Durães, Leonardo de Castro (2013)
PURPOSE: To evaluate the feasibility and safety of a new technique for laparoscopic segmental colectomy and primary anastomosis in the left colon of rats. METHODS: Thirty rats were randomly assigned to three groups of ten animals each. All animals underwent segmental resection of the left colon and end-to-end anastomosis. In Group I, the animals underwent laparoscopic surgery with carbon dioxide pneumoperitoneum at a pressure of 5 mmHg. In Group II, the animals underwent pneumoperitoneum with carbon dioxide at a pressure of 12 mmHg. In Group III, the control group, the animals underwent open surgery. All animals were reopened on the 7th postoperative day and were evaluated for peritonitis, abscesses, anastomotic dehiscence and bowel obstruction, and the anastomosis bursting pressure was measured. RESULTS: No obstructions, peritonitis or abscesses were found in any of the animals. An animal in Group I exhibited a blocked anastomosis leakage. The average anastomosis bursting pressure in the 30 animals was 187.02 ± 68.35 mmHg. There was no significant difference in the anastomosis bursting pressure among the groups (p = 0.503) CONCLUSION: The laparoscopic experimental model was feasible and safe for segmental colectomy and anastomosis of the left colon in rats.